An algorithm as a method of controlling the competitiveness of the entrepreneurial structures on the basis of the foresight projects (Путеводитель предпринимателя)
Is considered in the article the algorithm of control of the competitiveness of the entrepreneurial structures on the basis of the foresight project, which includes a number of sequential steps, with analytical and prognostic nature.